Management of seizures in neonates with neonatal encephalopathy treated with hypothermia. Issue 4 (August 2021) - DeLaGarza-Pineda, Oscar; Mailo, Janette A.; Boylan, Geraldine; Chau, Vann; Glass, Hannah C.; Mathur, Amit M.; Shellhaas, Renée A.; Soul, Janet S.; Wusthoff, Courtney J.; Chang, Taeun; ,
Abstract: Neonatal encephalopathy (NE) is the most common etiology of acute neonatal seizures – about half of neonates treated with therapeutic hypothermia for NE have EEG-confirmed seizures. These seizures are best identified with continuous EEG monitoring, as clinical diagnosis leads to under-diagnosis of subclinical seizures and over-treatment of events that are not seizures. High seizure burden, especially status epilepticus, is thought to augment brain injury. Treatment, therefore, is aimed at minimizing seizure burden. Phenobarbital remains the mainstay of treatment, as it is more effective than levetiracetam and easier to administer than fosphenytoin. Emerging evidence suggests that, for many neonates, it is safe to discontinue the phenobarbital after acute seizures resolve and prior to hospital discharge.